PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA TATANAN RUMAH TANGGA MASYARAKAT USING (Studi Kualitatif di Desa Kemiren, Kecamatan Glagah, Kabupaten Banyuwangi) - Husni Abdul Gani; Erdi Istiaji; Prita Eka Pertiwi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2015)
The research was proposed by Gani, et al (2013:12) about “Desain Kawasan Sehat untuk Wisata Budaya Using di Kabupaten Banyuwangi” was calculated the use of health toilet is 54%, the use of quite health toilet is 37%, and the use of not-health toilet is 9%. Furthermore, this research also calculated the behavior of using clean water is 94% and 63% not usingtrash can. The purpose of this study was to analyze PHBS Using community includes predisposing, enabling, reinforcing based on three indicators of PHBs that apply to defecate in latrines, using clean water, and dispose of waste in place. This research is a qualitative descriptive study. Some techniques of data collection are applied in this research; in-depth interview, documentation, and observation. Determination of the informants in this research used purposive technique. The results showed that people still have the habit Using defecate in the river, people using clean water sourced from mountain springs, the habit of not sorting garbage and dispose of garbage in the river. The village head required that every homeshould have latrines to reduce the habit of people to defecate in the river. Mother village heads who were members of the PKK had been doing counseling about recycling but the response was still not appropriate. There is a tradition in Kemiren rabo wekasan. This tradition bequeathed 1 cultural values that spring must be maintained by cleaning.Keywords : Healthy and Clean Lifestyles, Defecate, Clean Water, Trash